2015
DOI: 10.3354/cr01326
|View full text |Cite
|
Sign up to set email alerts
|

Variability of effects of spatial climate data aggregation on regional yield simulation by crop models

Abstract: Co-author addresses are provided in the Supplement (www. int-res. com/ articles/ suppl/ c065 p053 _ supp. pdf) ABSTRACT: Field-scale crop models are often applied at spatial resolutions coarser than that of the arable field. However, little is known about the response of the models to spatially aggregated climate input data and why these responses can differ across models. Depending on the model, regional yield estimates from large-scale simulations may be biased, compared to simulations with high-resolution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 67 publications
2
39
0
Order By: Relevance
“…The groups of models with medium and strong aggregation effects are all models that determine NPP based on the radiation use efficiency, while the other models use temperature based approaches. Hoffmann et al (2015) investigated the aggregation effect on yields for the same set of models and the same region and suggested that the aggregation effect on radiation may not be much higher than on temperature, but the models might be sensitive to changes on radiation values. Despite trends of decreasing temperature and solar radiation at coarser resolution ( Fig.…”
Section: Model Specific Aggregation Effectmentioning
confidence: 98%
See 4 more Smart Citations
“…The groups of models with medium and strong aggregation effects are all models that determine NPP based on the radiation use efficiency, while the other models use temperature based approaches. Hoffmann et al (2015) investigated the aggregation effect on yields for the same set of models and the same region and suggested that the aggregation effect on radiation may not be much higher than on temperature, but the models might be sensitive to changes on radiation values. Despite trends of decreasing temperature and solar radiation at coarser resolution ( Fig.…”
Section: Model Specific Aggregation Effectmentioning
confidence: 98%
“…The models were not calibrated for the study area, but were adjusted based on 30-year yield averages of about 8 t ha −1 for winter wheat and 14 t ha −1 for silage maize. The weather data, presented and discussed by Zhao et al (2015) and Hoffmann et al (2015), show a 30 year average temperature of 9.7 • C, an average annual precipitation of 899 mm and mean annual global radiation of 3758 MJ m −2 a −1 with the standard deviations of 1.2 • C, 214.0 mm a −1 and 169.4 MJ m −2 a −1 , respectively. The coldest year was 2004, with an average temperature of 8.9 • C and the warmest year was 1983 (11.2 • C).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations